Low mutation burden and frequent loss of CDKN2A/B and SMARCA2, but not PRC2, define premalignant neurofibromatosis type 1–associated atypical neurofibromas. Issue 8 (5th February 2019) - Pemov, Alexander; Hansen, Nancy F; Sindiri, Sivasish; Patidar, Rajesh; Higham, Christine S; Dombi, Eva; Miettinen, Markku M; Fetsch, Patricia; Brems, Hilde; Chandrasekharappa, Settara C; Jones, Kristine; Zhu, Bin; et al.
Abstract: Background: Neurofibromatosis type 1 (NF1) is a tumor-predisposition disorder caused by germline mutations in NF1 . NF1 patients have an 8–16% lifetime risk of developing a malignant peripheral nerve sheath tumor (MPNST), a highly aggressive soft-tissue sarcoma, often arising from preexisting benign plexiform neurofibromas (PNs) and atypical neurofibromas (ANFs). ANFs are distinct from both PN and MPNST, representing an intermediate step in malignant transformation. Methods: In the first comprehensive genomic analysis of ANF originating from multiple patients, we performed tumor/normal whole-exome sequencing (WES) of 16 ANFs. In addition, we conducted WES of 3 MPNSTs, copy-number meta-analysis of 26 ANFs and 28 MPNSTs, and whole transcriptome sequencing analysis of 5 ANFs and 5 MPNSTs. Results: We identified a low number of mutations (median 1, range 0–5) in the exomes of ANFs (only NF1 somatic mutations were recurrent), and frequent deletions of CDKN2A/B (69%) and SMARCA2 (42%). We determined that polycomb repressor complex 2 (PRC2) genes EED and SUZ12 were frequently mutated, deleted, or downregulated in MPNSTs but not in ANFs. Our pilot gene expression study revealed upregulated NRAS, MDM2, CCND1/2/3, and CDK4/6 in ANFs and MPNSTs, and overexpression of EZH2 in MPNSTs only. Conclusions: The PN-ANF transition is primarily driven by the deletion of CDKN2A/B. Further progression from ANF to MPNST likely involves broad chromosomal rearrangements and frequent inactivation of the PRC2 genes, loss of the DNA repair genes, and copy-number increase of signal transduction and cell-cycle and pluripotency self-renewal genes.